Prevalence and Factors Associated with Significant Rebound Hyperbilirubinemia after Phototherapy Among Neonates: A Cross Sectional Survey - Sindhu, Falak Naz, Manoj Kumar, Ambreen Raza, Muhammad Usman, Mahesh Lohana, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The study was conducted to determine the frequency of post-phototherapy rebound hyperbilirubinemia in neonates. Background: Serum total bilirubin is rapidly reduced in newborn hyperbilirubinemia following intensive phototherapy. With this approach, there is a worry that the bilirubin level frequently rises slightly after stopping phototherapy, a condition called as rebound hyperbilirubinemia. In preterm newborns, those receiving phototherapy for fewer than 72 hours, and those whose Coombs test is positive, post-phototherapy rebound hyperbilirubinemia occurs most frequently. Materials and Methods: A cross sectional survey was conducted in postnatal wards, NICU, Neonatal step down unit, and Pediatric wards at the Agha Khan University Hospital, Karachi, Pakistan from July to December 2016. Using a consecutive sampling method, 178 neonates were included in the study. Data included basic demographic information, along with the gestational age, gender, mode of delivery, and details of phototherapy. Besides, frequency, percentages and descriptive statistics, we employed Chi square test of association considering p-value ≤0.05 as significant. Results: There were 50.6% male and 49.4% female neonates. Total 15.7% neonates were found with rebound hyperbilirubinemiaMean age was 66.21±53.92 hours. Mean length of stay in hospital was 3.14±2.08 days. Mean phototherapy duration was 37.90±6.52 hrs. Practical implication: this study is done to check for rebound hyperbilirubinemia in neonates after phototherapy. Conclusion: Our study found 15.7% neonates with rebound hyperbilirubinemia and was also found significant with age at admission, birth weight, and hospital stay length. Keywords: Post-Phototherapy, Rebound Hyperbilirubinemia, Neonates, prevalance